Indigenous And Colonial Origins of Comparative Economic Development : The Case of Colonial India And Africa - Bayly, Christopher Alan, 1945-2015 1945-2015 (The World Bank, 2008)
This paper concerns the institutional origins of economic development, emphasizing the cases of nineteenth-century India and Africa. Colonial institutions-the law, western style property rights, newspapers and statistical analysis-played an important part in the emergence of Indian public and commercial life in the nineteenth and twentieth centuries. These institutions existed in the context of a state that was extractive and yet dependent on indigenous cooperation in many areas, especially in the case of the business class. In such conditions, Indian elites were critical in creating informal systems of peer-group education, enhancing aspiration through the use of historicist and religious themes and in creating a "benign sociology" of India as a prelude to development. Indigenous ideologies and practices were as significant in this slow enhancement of Indian capabilities as transplanted colonial ones. Contemporary development specialists would do well to consider the merits of indigenous forms of association and public debate, religious movements and entrepreneurial classes. Over much of Asia and Africa, the most successful enhancement of people's capabilities has come through the action of hybrid institutions of this type